Cancer mortality predictions for 2021 in Latin America. Issue 3 (8th July 2021) - Carioli, Greta; Bertuccio, Paola; Malvezzi, Matteo; Boffetta, Paolo; Levi, Fabio; Negri, Eva; La Vecchia, Carlo
Abstract : We estimated cancer mortality statistics for the current year in seven major Latin American countries, with a focus on colorectal cancer. We retrieved official death certification data and population figures from the World Health Organization and the Pan American Health Organization databases. We analysed mortality from all neoplasms combined and for selected cancer sites. We estimated numbers of deaths and age-standardized mortality rates for the year 2021 using a logarithmic Poisson count data joinpoint model. Total cancer mortality is predicted to decline in all countries considered for both sexes, with the exception of Argentinian women. The lowest total mortality rates were predicted in Mexico (65.4/100 000 men and 62.3 in women), the highest ones were in Cuba (133.3/100 000 men and 91.0 in women). Stomach cancer rates have been decreasing since 1970 in all countries; colorectal cancer started to decline over recent calendar periods. Rates for this cancer were unfavourable in the youngest age group. Lung cancer trends declined in males and remained comparatively low in all countries except Cuba. In Cuba, lung cancer rates in women overtook those for breast. Mortality from cancers of the breast, (cervix) uterus, ovary, prostate and bladder, as well as leukemia mostly showed favourable trends. A marked variability in rates across Latin American countries persists, and rates were relatively high for stomach, uterus, prostate and lung cancers, as compared to Europe and North America, suggesting the need to improve preventive strategies. Colorectal cancer mortality was relatively low in Latin America, except in Argentina, and short-term predictions remain moderately favourable.